La colonie italienne en Égypte entre 1861 et 1914 : élites, émigration de masse et dissidence politique dans un des pays du Levant et de Barbarie - Costantino Paonessa (Cahiers d’histoire)
This article explores the relationship between emigration and colonialism through an articulated reading of the history of the Italian colony of Egypt in the period between the unification of Italy and the eve ofWorld War one. It examines the role of the various actors who made up the colony and how their involvement helped to maintain the privileges derived from the legal system of the Capitulations. Through the study of numerous archival documents, the article highlights the threads linking the political, social and cultural processes that, outside Italy, underpinned the debate around Italian « national identity », at a time when the political commitment of the subaltern classes was developing.